a² == a | b² == b | c² == c | a + b + c = 0, |
Proof: Assume that , a, b and c are as in the hypothesis above. Let be the unique algebra homomorphism from the noncommutatve polynomial ring C[x, x, x] into defined by (x) = a, (x) = b and (x) = c. Since a, b and c are as in the hypothesis above, the kernel of contains the polynomials
x - x | x - x | x - x | x + x + x. |
YOUR SESSION HAS DIGESTED | ||
---|---|---|
THE FOLLOWING RELATIONS | ||
x 0
x 0
USER CREATIONS APPEAR BELOW | ||
---|---|---|
SOME RELATIONS WHICH APPEAR BELOW | ||||
---|---|---|---|---|
MAY BE UNDIGESTED | ||||
Therefore, x, x, x lie in the kernel of . Since a = (x), b = (x) and c = (x), a = 0, b = 0 and c = 0.